Anthranilate at the interface of tryptophan and specialized metabolite biosynthesis - Holland, Cynthia K.; Watson, Aracely P.; Chiang, Ellia (Frontiers in Plant Science, 2025)
Plants synthesize a diverse array of specialized metabolites that contribute to plant development, growth, protection from biotic and abiotic stressors, and attracting pollinators and seed dispersers. Specialized metabolites are often derived from primary metabolites, such as amino acids, but also can be redirected from intermediates in primary metabolic pathways. In the L-tryptophan (Trp) biosynthetic pathway, the intermediate anthranilate is siphoned away to synthesize volatiles and specialized metabolites. Methyltransferases can produce the O-methyl ester of anthranilate, a grape aroma volatile produced in species such as grapevine, strawberry, citrus, maize, and soybean. O-Methyl anthranilate serves context-dependent roles in attracting insects and deterring herbivores. Methylation at the amine generates N-methyl anthranilate, a precursor for N-methyl anthranilate esters in citrus and antimicrobial avenacins in black oat. This Mini Review explores the regulation of anthranilate within the context of the Trp pathway and its contributions to the biosynthesis of anthranilate-containing volatiles and specialized metabolites. Also highlighted are the roles of anthranilates in plant defensive metabolism and the substrate specificity of anthranilate-using enzymes, as well as unanswered questions about the synthesis, transport, and physiological role of anthranilates.